IT and Tourism Business - Do Serbian Companies in Tourism Follow Contemporary Trends? - Brdar, Ivana; Gajić, Jelena (Industrija, 2019)
Information technologies are important both for the strategic and operational activities in the tourism and hotel industry. They simultaneously represent opportunities, but also challenges, especially when it comes to the uncertainty of their dynamic development. Since all participants in the tourism and hotel industry compete for an attractive position in the market, IT usage is a must in this process whether it is: internal and external business operations, IT applications for the process of managing business operations and marketing activities or communication with the target groups in a global environment. The aim of the paper is to determine the differences in the degree and method of using IT by the accommodation capacities and tourist agencies (travel agencies and tour operators) in Serbia. In the research conducted in 2017, 209 companies participated, of which 99 were accommodation facilities (hotels, private accommodation, hostels, etc.) and 110 travel agencies and tour operators. Pearson chi square test was used to assess significant differences between groups in terms of nominal data and Mann-Whitney U test for ordinal data. The results showed that Serbian companies use IT in everyday business, but that there are certain differences in the use of different tools and IT capabilities.
Keywords: Serbia; Touroperators; Travel agencies; Accommodation facilities; Information technology; Tourism